2006
DOI: 10.1073/pnas.0605298103
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent induction of microRNA miR-146, an inhibitor targeted to signaling proteins of innate immune responses

Abstract: Activation of mammalian innate and acquired immune responses must be tightly regulated by elaborate mechanisms to control their onset and termination. MicroRNAs have been implicated as negative regulators controlling diverse biological processes at the level of posttranscriptional repression. Expression profiling of 200 microRNAs in human monocytes revealed that several of them (miR-146a͞b, miR-132, and miR-155) are endotoxin-responsive genes. Analysis of miR-146a and miR-146b gene expression unveiled a patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

205
4,125
15
38

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 3,925 publications
(4,447 citation statements)
references
References 45 publications
205
4,125
15
38
Order By: Relevance
“…In particular, the miRNA-146a has been specifically associated with the regulation of TLR signaling (Cui et al, 2010;Quinn and O'Neill, 2011;Sheedy and O'Neill, 2008;Taganov et al, 2006). miRNA146a is expressed in human brain, and astrocytes have been shown to be key players in the regulation of this miRNA in response to inflammatory molecules, such as IL-1b Cui et al, 2010).…”
Section: Astrocytes As Source and Target Of Inflammatory Moleculesmentioning
confidence: 99%
“…In particular, the miRNA-146a has been specifically associated with the regulation of TLR signaling (Cui et al, 2010;Quinn and O'Neill, 2011;Sheedy and O'Neill, 2008;Taganov et al, 2006). miRNA146a is expressed in human brain, and astrocytes have been shown to be key players in the regulation of this miRNA in response to inflammatory molecules, such as IL-1b Cui et al, 2010).…”
Section: Astrocytes As Source and Target Of Inflammatory Moleculesmentioning
confidence: 99%
“…Recent studies have revealed that miR‐146 is primarily involved in the regulation of inflammation and other processes that function in the innate immune system (Sonkoly, Stahle & Pivarcsi, 2008). miR‐146a has been shown to be a circulating miRNA that is increased in synovial tissues and fibroblasts in rheumatoid arthritis (RA) patients as a particularly important negative regulator of nuclear factor‐κB (NF‐κB) signaling (Murata et al., 2010; Stanczyk et al., 2008; Taganov, Boldin, Chang & Baltimore, 2006). miR‐146a has also received much attention in the field of OA research.…”
Section: Introductionmentioning
confidence: 99%
“…12 MiR-146a and miR-146b-5p are well studied miRs with multiple targets, whose gene and processing are rather well known. MIR146A (MIM# 610566) has two exons separated by a~16 kb intron 13,14 and is transcribed into a pri-miR of 2329 nt (GenBank accession number: EU147785.1); exon 2 contains the sequence of the pre-miR, which starts 53 nt from its 5ʹ-end. MIR146B (MIM# 610567) has only one exon and the transcription start site is located~700 nt upstream of the mature miR-146b-5p sequence, 14 but is not defined precisely, nor is identified the polyadenylation site.…”
Section: Introductionmentioning
confidence: 99%